Meningkatkan Kemampuan Sosial Emosional Anak Usia Dini Melalui Bermain - Aulia Nur Az-Zahra; Desvi Wahyuni (CV. Ulil Albab Corp, 2023)
Children's social emotional development is a child's sensitivity to understanding other people's feelings when interacting in everyday life. The child's level of interaction with other people starts from parents, siblings, playmates to the wider community. This research aims to improve the social emotional abilities of young children through play. The method used in this research is literature study research. Literature study in this research is a series of activities relating to methods of collecting library data, reading and taking notes, and managing research data objectively, systematically, analytically and critically